CBP Bromodomain Inhibition Rescues Mice From Lethal Sepsis Through Blocking HMGB1-Mediated Inflammatory Responses - Bi, Xiaowen; Jiang, Baolin; Zhou, Jinyi; Fan, Xirui; Yan, Xintong; Liang, Juanjuan; Luo, Lan; Yin, Zhimin (Frontiers in Immunology, 2021)
CREB binding protein (CBP), a transcriptional coactivator and acetyltransferase, is involved in the pathogenesis of inflammation-related diseases. High mobility group box-1 protein (HMGB1) is a critical mediator of lethal sepsis, which has prompted investigation for the development of new treatment for inflammation. Here, we report that the potent and selective inhibition of CBP bromodomain by SGC-CBP30 blocks HMGB1-mediated inflammatory responses in vitro and in vivo. Our data suggest that CBP bromodomain inhibition suppresses LPS-induced expression and release of HMGB1, when the inhibitor was given 8 h post LPS stimulation; moreover, CBP bromodomain inhibition attenuated pro-inflammatory activity of HMGB1. Furthermore, our findings provide evidence that SGC-CBP30 down-regulated rhHMGB1-induced activation of MAPKs and NF-κB signaling by triggering the reactivation of protein phosphatase 2A (PP2A) and the stabilization of MAPK phosphatase 1 (MKP-1). Collectively, these results suggest that CBP bromodomain could serve as a candidate therapeutic target for the treatment of lethal sepsis via inhibiting LPS-induced expression and release of HMGB1 and suppressing the pro-inflammatory activity of HMGB1.